2003
DOI: 10.1046/j.1365-2044.2003.03403.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of bispectral index and ARX‐derived auditory evoked potential index in measuring the clinical interaction between ketamine and propofol anaesthesia

Abstract: SummaryWe evaluated the effects of a bolus (0.4 mg.kg )1 ) and continuous infusion (1 mg.kg )1 .h )1 ) of ketamine on Bispectral Index (BIS) and A-LineÒ ARX Index (AAI) during propofol anaesthesia. We included 15 ASA I patients scheduled for general anaesthesia. Induction was performed by infusion of propofol at 100 ml.h )1 until loss of consciousness. Both BIS and AAI monitors responded appropriately at that time. The calculated effect site concentration of propofol at loss of consciousness was maintained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 18 publications
3
47
0
Order By: Relevance
“…Additionally, Hirota et al [10] have previously showed that a ketamine bolus of 0.4 mg/kg significantly increases the BIS values during propofol-fentanyl anaesthesia. Vereecke et al [9] presented the same effects on the BIS values after a ketamine bolus of 0.4 mg/kg followed by a 1 mg/kg/h continuous infusion. Hans et al [13] concluded that a ketamine bolus of 0.5 mg/kg also significantly increases the BIS values, during a sevoflurane anaesthesia.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…Additionally, Hirota et al [10] have previously showed that a ketamine bolus of 0.4 mg/kg significantly increases the BIS values during propofol-fentanyl anaesthesia. Vereecke et al [9] presented the same effects on the BIS values after a ketamine bolus of 0.4 mg/kg followed by a 1 mg/kg/h continuous infusion. Hans et al [13] concluded that a ketamine bolus of 0.5 mg/kg also significantly increases the BIS values, during a sevoflurane anaesthesia.…”
Section: Discussionsupporting
confidence: 48%
“…Consequently, several authors have assessed the effect of different analgesic doses of ketamine in BIS values [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, S(+)-ketamine is suited to reach equal effects in sedation as fentanyl, which contrasts the result of other studies, where an increase of BIS was seen after administration of ketamine. 45,46 CONCLUSIONS S(+)-ketamine with BIS monitoring provides adequate and controllable sedation in neurosurgical patients.…”
Section: Discussionmentioning
confidence: 98%
“…Bispectral index (BIS) is widely used to guide the administration of hypnotic drugs. Despite a deepening level of hypnosis, several studies have reported an increase in BIS values when 0.5 mg kg -1 ketamine is administered as a rapid bolus during general anaesthesia (32,33). Therefore, we did not use BIS for assessment of the level of hypnosis during induction.…”
Section: Discussionmentioning
confidence: 99%